A new species of Maladera Mulsant & Rey, 1871 from Iran (Coleoptera: Scarabaeidae: Sericini) and a review of the distribution of the genus in Iran. Issue 4 (2nd October 2018) - Fabrizi, Silvia; Rößner, Eckehard; Ahrens, Dirk
Abstract : A new species of Maladera Mulsant & Rey, 1871 is described from Iran: M. kermanensis sp. n. The habitus and genitalia of the new species are illustrated. Additional records of Maladera species and a checklist of the species occurring in Iran including a map of their distribution are given. http://www.zoobank.org/urn:lsid:zoobank.org:pub:812B8D62-2DD5-42CF-8BCD-F576CF3D2A7E